Program Parenting: Kelas Pertemuan Orang Tua (KPO) dan Keterlibatan Orang Tua dalam Kelompok atau Kelas Anak (KOK) - Lucia Seftiana Utami; Mutiara Fajar; Febi Purwanti; Yecha Febrieanitha Putri (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research was motivated by the parenting class parent meeting program (KPO), and parental involvement in groups or classes (KOK). So that the knowledge and understanding of parents in the process of educating and caring for children in the family. The aims of this study are (1) to describe what parent meeting class activities are. (2) to describe the implementation of parent meeting class activities, (3) to describe the purpose of parent meeting class activities, (4) to describe parent interactions in groups/ children's classes, (5) descriptions of parental interactions in children's groups/classes. (6) describing parental interactions in children's groups/classes. Data collection techniques were carried out using document studies. The results of the research aimed at involving parents in the process of children's education in open and transparent schools.